Multimodal meaning making in news communication about immigration: using the NewsScape corpus to explore co-verbal images in TV news - Hart, Christopher (Frontiers in Communication, 2024)
The communication of news relies on semiotic resources besides language, including various audiovisual modes of representation. Owing to the difficulties associated with obtaining televisual data, the vast majority of research addressing multimodality in the news has been targeted at print news media, where various strategies in visual representation and patterns of interaction between verbal and visual modes have been discerned. Where televisual data has been interrogated, this has been based on a very limited number of data points. In this study, I exploit the NewsScape library -a massive multimodal corpus of news communication -to investigate multimodal representations of immigration in television news. Accessible via CQPWeb, the corpus is searched for target utterances refugees/(im)migrants have VERBed and refugees/(im)migrants are VERBing. The co-verbal images accompanying 474 utterances describing motion events are analysed quantitatively and qualitatively. Among the results discussed are that refugees/migrants are depicted in large rather than small groups, that they are depicted in transit somewhere along the migratory journey rather than in countries of origin or destination countries, that they are depicted on land more than at sea, that they are depicted in security contexts, and that they are erased represented instead through abstract forms such as maps. Differences in the visual representation of people designated as 'refugee' versus 'migrant' are also observed and discussed.